A Genetic Code Expansion‐Derived Molecular Beacon for the Detection of Intracellular Amyloid‐β Peptide Generation - Sappakhaw, Khomkrit; Jantarug, Krittapas; Slavoff, Sarah A.; Israsena, Nipan; Uttamapinant, Chayasith (Angewandte Chemie International Edition, 2021)
Polypeptides generated from proteolytic processing of protein precursors, or proteolytic proteoforms, play an important role in diverse biological functions and diseases. However, their often‐small size and intricate post‐translational biogenesis preclude the use of simple genetic tagging in their cellular studies. Herein, we develop a labeling strategy for this class of proteoforms, based on residue‐specific genetic code expansion labeling with a molecular beacon design. We demonstrate the utility of such a design by creating a molecular beacon reporter to detect amyloid‐β peptides, known to be involved in the pathogenesis of Alzheimer's disease, as they are produced from amyloid precursor protein (APP) along the endocytic pathway of living cells. Biogenesis of amyloid‐β peptides from their precursor protein can be tracked in endocytic compartments of living cells by a molecular beacon labeling strategy based on genetic code expansion.